Is Qi Fu Yin effective in clinical treatment of dementia?: A meta-analysis of 697 patients. Issue 5 (5th February 2021) - Wang, Lei; Qiao, Pengli; Yue, Lulu; Sun, Rong
Abstract: Background: Dementia, a kind of acquired and progressive intelligence-damaging syndrome, is induced by cerebral dysfunction. Ancient records show that Qi Fu Yin (QFY) has the advantages in age-related dementia treatment. This study aims to evaluate therapeutic efficacy of QFY on dementia through meta-analysis. Methods: We comprehensively reviewed articles from various databases, including China National Knowledge Infrastructure (CNKI), Wanfang, VIP, Chinese Biomedical Literature (CBM), PubMed, and Web of Science published before June 2020, for all randomized controlled trials (RCTs) on dementia treatment with QFY. Then, we selected eligible literatures, extracted related data, and assessed risk of bias. Forest plots of total clinical effective rate, MMSE score, HDS score and ADL score illustrated the difference between the experimental group (treatment with QFY alone or combined with routine western medicine) and the control group (treatment with routine western medicine only). Random effects model and fixed effects model were adopted. Finally, publication bias was further analyzed using funnel plot, sensitivity analysis, Begg and Egger test. Results: Finally, 9 RCTs, involving 697 patients, were included in this study. The results revealed that the total clinical effective rate of the experimental group was obviously higher than that of the control group (OR = 0.33, 95% CI [0.22, 0.50], P  < .001). In comparison with the control group, the experimental group showed higher MMSE score (WMD = 2.60, 95% CI [2.16, 3.03], P  < .001) and HDS score (WMD = 1.51, 95%CI [1.10, 1.92], P  < .001). Due to few included studies, there were no statistically significance between experimental and control groups (WMD = -9.90, 95%CI [−26.09, 6.30], P  = .231) regarding ADL score. In addition, there is no publication bias towards clinical effective rate and MMDE score. Conclusions: QFY only or combined with western medicine therapy can significantly improve cognitive ability compared with only western medicine therapy in dementia. However, multiple samples, RCTs of high quality are still needed to verify our conclusions.